Legacy of Engagement in Southeast Asia - Welsh, Bridget, 1971-; Murphy, Ann Marie (Book collections on Project MUSE., 2008)
This rich collection of essays explores the dramatic political, economic, and social transformations in Southeast Asia since 1945. Academics and practitioners trace three themes - transformations within Southeast Asian countries, the actors and processes that contributed to these changes, and new dynamics in foreign relations. These diachronic essays examine how engagement among Southeast Asians and between regional and outside actors have affected patterns of democracy, and development.